Structure and function of the foregut and salivary glands of the synanthropic diplopod Urostreptus atrobrunneus (Spirostreptidae) - de Sousa, Cristina Moreira [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Brill Academic Publishers, 2012)
Diplopods are considered to be important macro-arthropods of the soil because they are involved in maintaining the balance of the ecosystem. Normally, they do not maintain a large population, but population explosions may occur due to environmental imbalances, climate changes and the use of pesticides that can eliminate possible competitors. The millipede Urostreptus atrobrunneus Pierozzi and Fontanetti, 2006 has infested sites in urban centers of São Paulo State, causing various problems for the human population; the lack of knowledge of this millipede's biology has hindered efforts to efficiently control the infestation. Because of this lack of knowledge, this study aims to contribute to the understanding of this pest, describing the morphology of the foregut and salivary glands of the millipede U. atrobrunneus, and relating them to their respective functions by histological and histochemical analyses.
Keywords: Millipede; Diplopoda; digestion; digestive enzymes